Celiac Disease and Serious Infections: A Nationwide Cohort Study From 2002 to 2017. (7th October 2022) - Röckert Tjernberg, Anna; Mårild, Karl; Söderling, Jonas; Lebwohl, Benjamin; Roelstraete, Bjorn; Bonnedahl, Jonas; Green, Peter H.R.; Ludvigsson, Jonas F.
Abstract : INTRODUCTION: Patients with celiac disease (CD) have an increased risk of encapsulated bacterial infections. Less is known about other serious infections in CD, especially in patients diagnosed in the 21st century. METHODS: We contacted all 28 pathology departments in Sweden through the Epidemiology Strengthened by histoPathology Reports in Sweden (ESPRESSO) cohort study and identified 20, 088 individuals with CD (defined as villous atrophy) diagnosed in 2002–2017. Patients were matched for sex, age, and calendar year to 80, 152 general population comparators and followed up until December 31, 2019. Serious infections were defined as having a hospital-based (inpatient and outpatient) diagnosis in the National Patient Register. Cox regression yielded adjusted hazard ratios (aHR) controlling for education, country of birth, and comorbidities. RESULTS: During 173, 695 person-years of follow-up, 6, 167 individuals with CD (35.5/1, 000 person-years) had a serious infection. This was compared with 19, 131 infections during 743, 260 person-years (25.7/1, 000 person-years) in matched comparators, corresponding to an aHR of 1.29 (95% confidence interval [CI] = 1.25–1.33). aHR were similar when restricted to infection requiring hospital admission (1.23; 95% CI = 1.17–1.29). The excess risk of serious infections also persisted beyond the first year after CD diagnosis (aHR = 1.24; 95% CI = 1.20–1.29). Patients with CD were at risk of sepsis (aHR = 1.26; 95% CI = 1.09–1.45) and gastrointestinal infections (1.60; 95% CI = 1.47–1.74). Mucosal healing during CD follow-up did not influence the risk of subsequent serious infections. DISCUSSION: This nationwide study of patients with celiac disease diagnosed in the 21st century revealed a significantly increased risk of serious infections. While absolute risks were modest, vaccinations should be considered during CD follow-up care.